Determinan Keputusan Nasabah Menabung di BTN Syariah KC Solo dengan Minat Sebagai Variabel Intervening - Cahyani, Ajeng Regita; Guritno, Agung (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study was to determine the factors that influence customer decisions to save at Islamic banks with customers interest as an intervening variable. The research method uses an associative descriptive quantitative approach. The number of samples was 100 respondents of Islamic bank customers. data collection techniques using questionnaires. The results showed that profit sharing rate, bank reputation, religiosity and interest directly had a positive effect on customer saving decisions at BTN Syariah. Then the profit sharing rate, reputation and religiosity have a positive effect on customer interest in saving at BTN Syariah. Interest variables are also unable to mediate the effect of profit sharing rate, reputation and religiosity on customer decisions indirectly